Expanding Higher Education: China's Precarious Balance. (14th December 2020) - Postiglione, Gerard A.
Abstract: China implemented an unprecedented expansion of higher education along with excellence initiatives that propelled more universities into the global rankings. Yet, the international influence of the higher education system pales in comparison to its economy. This paper argues that governance reforms in higher education only partially address the increasingly complex social and geopolitical realities. With more institutional and professional autonomy, universities and the academic research enterprise would be better placed and more inclined to find innovative solutions to urgent problems of domestic and global sustainability.